IMPLEMENTASI PENDEKATAN BIOPHILIC DESIGN PADA RANCANG BENTUK DAN RUANG BANGUNAN APARTMENT DI KAWASAN CBD GEM CITY GRESIK - Andi Prasetyo Bakti; Firdha Ayu Atika; Siti Azizah (Prosiding Seminar Nasional Sains dan Teknologi Terapan, 2022)
Most of the land in Manyar District, Gresik Regency is in the form of agricultural land and cultivated land, along with increasing population growth and the transfer of land use functions as residential areas and industrial areas. In this case, it can cause ecological damage, including a decrease in land productivity, a crisis in rainwater storage areas, and so on. The increase in population growth is very significant, resulting in the expansion of the housing and industrial sectors. Especially East Java Province, one of the provinces based on manufacturing because the existing industry is able to contribute to the regional economy by 40 percent. With the establishment of several companies in integrated industrial areas, it is believed that they will be able to have a chain effect on national and regional economic growth. In the GEM City area there is the Central Business District area which is the center of the Business district. Related to problems in the site environment, Office Tower Apartment is used as a residential area that is directly integrated with the industrial area. Therefore, planning and designing an apartment with an environmentally friendly theme with the aim of becoming a residence that responds to the typology of the surrounding environment and presents green space to improve the quality of life. This research uses architectural planning and design methods based on observations from comparative studies by analyzing related objects and conducting questionnaires for residential enthusiasts in apartments. From the results of the study, it can be concluded that the apartment in the CBD GEM City uses the theme of Biophilic Design, especially in the form of the building by applying the concept of Responsive with Nature and in the design of the building space applying the concept of Efficiency.